ECONOMIC IMPACT OF THE 2018 MAHARASHTRA PLASTIC BAN ON PLASTIC WASTE MANAGEMENT IN NAGPUR CITY (2020-21) - Hukare, Alka V.; Tekade, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The 2018 Maharashtra Plastic Ban, enacted on March 23, 2018, targeted single-use plastics to mitigate environmental degradation and reduce waste management burdens in urban centers like Nagpur City. This study investigates the ban’s economic impact on Nagpur’s plastic waste management system during 2020-21, leveraging verified data from the Central Pollution Control Board (CPCB, 2021)—14,250 tons per annum (TPA) total plastic waste and 565 TPA recyclable—and a landfill tipping fee of Rs 750 per tons (Times of India, 2016). By analyzing the ban’s reported 15% waste reduction (2,515 TPA, Tekade, 2020) and contributions from recycling efforts, the research quantifies economic benefits through cost savings. Results indicate Rs 18.86 lakh in annual landfill savings from reduced waste volumes and an additional Rs 4.24 lakh from diverting 565 TPA via recycling, yielding a total economic benefit of Rs 23.1 lakh for 2020-21. Contextualized against the Nagpur Municipal Corporation’s (NMC) Rs 96.22 crore investment in waste management infrastructure (Times of India, 2016), these savings represent a modest yet significant 0.24% cost recovery, underscoring the ban’s fiscal efficacy. The analysis employs straightforward cost calculations (quantity × unit cost) to highlight how waste reduction and recycling alleviate municipal expenditure. This study offers NMC and policymakers’ actionable insights to optimize waste management strategies economically, emphasizing the ban’s pivotal role in reducing disposal costs and supporting sustainable urban development. It also lays the groundwork for future research into long-term economic trends and enhanced recycling initiatives in Nagpur.